Social Media Ethics in the Context of Islamic Communication Review of the Qur'an and As Sunnah - Sa; Panuluh, Banyu Biru Intan; Maria, Chelsea Sivana Sofie (Budapest International Research and Critics University, 2021)
In the era of globalization, the process of delivering a message and receiving it is so fast and easy. This is evidenced by the existence of social networking applications that are present on smartphones. The use of social media is very diverse, so that many people, ranging from ordinary people to journalists, can spread what they want. However, unfortunately, sometimes there are those who spread information on social media who do not pay attention to communication ethics, causing untrue news such as hoaxes, defamation, denunciation, etc. all of which are out of the realm of ethics. Whereas in Islam really uphold ethics in communication and prioritize ethics. And in principle, it leads people to experience a peaceful and comfortable life. So as media users must apply ethics, one of these ethics is the principle of Islamic communication, in which this Communication has fourmain points, namely; honest, positive message, tabayyun and silm. Which Islamic communication has two main sources, namely the Al-Quran and As-Sunnah.